PENGARUH GAYA KEPEMIMPINAN, BUDAYA K3, PELATIHAN K3 TERHADAP KINERJA KARYAWAN DI PT. PLN (PERSERO) UP3 JEMBER - Agung Suprihandoyo; Ike Kusdyah Rachmawati; Yunus Handoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
An organization can run effectively if the management functions such as planning, organizing, motivation, discipline and supervision within it function well, and the supporting elements are available and meet the requirements. One of the most important elements that can support the running of the company is human resources (employees). Laborers, employees, workers or staff who essentially have the same goal to achieve an organizational or company goal. PT PLN (Persero) In order to maintain and improve corporate performance, PLN management sets Key Performance Indicators (KPI) as a benchmark for performance achievement that must be met by management and all lines of office every year. With this problem, the researcher wants to examine the leadership style, OHS culture, OHS training on employee performance at PT. PLN (Persero) UP3 Jember and the results obtained are that leadership style has a unidirectional and positive relationship with employee performance, OHS culture has a unidirectional and positive relationship with employee performance and OHS training has a unidirectional and positive relationship with employee performance.